0 голосов
14 просмотров
от Одаренный (2.9k баллов) в категории Алгебра

решить уравнения:

7(1-х) = (2х+3)(1-х)

|х²-4| = 3

2 Ответы

0 голосов
от Одаренный (1.5k баллов)
 
Лучший ответ

7-7х = 2х-2х^2+3-3х
2х^2-6х+4=0 | разделим все на 2
х^2-3х+2=0
D=9-4*2
D=1
x1=(3+1)/2=2
x2=(3-1)/2=1

x^2-4=3
x^2=7
x=+ и - корень из 7

-х^2+4=3
-х^2=-1
х^2=1
х= + и - 1

0 голосов
от (26 баллов)

7(1-x)=(2x+3)(1-x) 

7-7x=2x-2x²+3-3x

-7x-2x+2x²+3x=3-7

-6x+2x²=-4

-4x²=-4

x²=-4:-4

х²=1

 

 

 

 

 

 

 

...